Analyzing the Impact of Creative Self-Efficacy, Leadership Style, Locus of Control, and Organizational Culture on Innovative Work Behavior and Employee Performance - Rizqi Arianto Caesar Azeem; Syarifa Hanoum (Borong Newinera Publisher, 2024)
This research aims to explore the impact of various variables, including creative self-efficacy, leadership style, locus of control, organizational culture, innovative work behavior, and employee performance within a mining contractor company, named SIS. The research adopts a quantitative approach, and the sample consists of 111 respondents, specifically Production Group Leaders from SIS. Data were collected through a questionnaire and analyzed using Structural Equation Modeling (SEM) with the SEM PLS program. The findings of the study reveal the following relationships: (1) Creative self-efficacy significantly and positively influences innovative work behavior, (2) Creative self-efficacy significantly and positively influences employee performance, (3) Leadership style significantly and positively influences innovative work behavior, (4) Leadership style significantly and positively influences employee performance, (5) Locus of control significantly and positively influences innovative work behavior, (6) Locus of control significantly and positively influences employee performance, (7) Organizational culture significantly and positively influences innovative work behavior, (8) Organizational culture significantly and positively influences employee performance, and (9) Innovative work behavior significantly and positively influences employee performance. These results provide valuable insights for the mining contractor industry, offering implications for enhancing creative self-efficacy, leadership styles, locus of control, organizational culture, innovative work behavior, and ultimately, employee performance.